What is the deadline in accordance with the Constitution by which the President must appoint to а Prime-minister candidate a mandate for formation of a regular Government - Slavov, Peter (Law Journal of New Bulgarian University, 2023)
This article provides an analysis of case with the possible delay of the deadline within which the President of the Republic is obliged to appoint a mandate for formation of a Government as to art. 99. There is no explicit deadline in the Constitution, by which the latter must appoint the mandate, as e.g. he is obliged by art. 75 to convene the newly elected Parliament within 1-month-term. The case is especially important as there is no practice of the Constitutional Court on this matter, while there are quite a few rulings on the other aspects of art. 99 and the applicable terms after the first mandate has been appointed. While there are also some gaps in the constitutional framework, the Constitutional Court has adopted the term “reasonable term”, beyond which any delay shall be in contradiction with the Constitution. Precisely this “reasonability” in the context of appointing the first mandate will be analysed, in the context of the entire constitutional regulation of art. 99 for forming a regular Government but also in the spirit of a parliamentary Republic.